Fatigue of the Patient with Cancer: a systematic review - Júlia Barbosa da Fontoura Gonzalez; Maria Isabel Pinto Coelho Gorini (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
Cancer is one of the most prevailing chronic diseases in Brazil and in the world. However, the utilized treatments may develop numberless collateral effects. Since the last decade, the symptom of fatigue has been associated directly with cancer and its treatments and has become the object of study in this field. This systematic review was elaborated with the objective of analyzing scientific articles about the fatigue of patients with cancer in the years between 2002 and 2006, in connection with nursing and through the descriptors fatigue, cancer and nursing from the data base of MEDLINE, LILACS and BDENF. This study sampled 27 articles whose authors counted on one nurse at least. The analysis comprised types of cancer and of treatment, the use of scales for measuring fatigue, the methodology, outline of the study, the place and the publication periodical. The results of this study point out to the need of improving the knowledge about fatigue considering that it is a subject still little known by health professionals; it also evidences the need of availing such knowledge and of giving continuity to further investigations in order to clear up better the results of the interventions and to lead to softening such debilitating symptom.